Comparison of the World's Biggest e-Tailing Companies : Amazon and Alibaba - Farzaliyev, Siyavush (2021)
The research was aimed at analysing the marketing perspectives and communication tools of Alibaba and Amazon. Firstly, to reach the goal, there was used the secondary research based on already existing online and offline publications such as books, WebSimilar, Statista and others. Secondly, to conduct an in-depth analysis, the author used the primary research by preferring the usability testing on 6 participants to analyse their consumer behaviour on purchasing wireless mouses from the online stores of Alibaba and Amazon. Concerning the analyses on marketing and communication channels, it was revealed that Amazon completely outstrips its rival, Alibaba, in all components wherein the popular marketing tools for both companies were identified as straight visit to store and branded search terms. Concerning the usability testing, the factors such as user-interface, page layout, price, shipping costs and duration were taken into consideration, thus Amazon outstripped Alibaba by satisfaction level.